Studi penerapan Fish Feender Deeper Pro sebagai alat bantu penangkapan ikan oleh nelayan tangkap di Pulau Barrang Caddi - Fathahillah Fathahillah; Zulhajji Zulhajji (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The results of the assessment on the technology offishing assistance using Deeper Pro fish radar by capturefishermen on Barrang Island Caddi are the objectives of thispaper. The results of the study are reviewed in terms offunctional and usability. The results of the study show thatDeeper pro as a fish radar tool is effective in detecting thepresence of fish in the sea depth up to 80 meters. The amountof fish at a certain depth can be detected in the form of visualillustrations both in number and depth. The use of features inDeeper Pro can be easily mastered by fishermen catchingBarrang Caddi. The Deeper Pro fish radar device is functionaland usability usable in use by barrang caddi fishermen inassisting fish skill.